THE CONCEPT OF DEVELOPMENT AND CURRENT TOPICAL ASPECTS OF THE DISTANCE LEARNING SYSTEM IN AZERBAIJAN - Allahyarova, Tahira (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The present paper aims to review distance learning. There is noted that with the development of modern technologies, the channels for transmitting information and knowledge are also expanding. The rapid development of telecommunications creates ample opportunities for knowledge acquisition and greatly facilitates this process. In such conditions, distance education has a wider scope of application. Distance learning allows anyone, even in the most remote part of the world, regardless of income level, to take courses at the most prestigious universities. The article touches upon the current issues of distance education in Azerbaijan in modern times. Trying to answer this question: What current trends are observed in distance education and what forms of it are used in Azerbaijan? The author notes that distance learning, which began to be applied during the pandemic, has created a negative public opinion about education to some extent: «If remote, then poor quality». Currently the most serious problem is to change the opinion formed in society. Today, distance education should be perceived as inevitable step in terms of solving the crisis emanating from the pandemic. This is also a non-alternative approach from the standpoint of ensuring the sustainability of education. As a result, it is concluded that education definitely needs to change. This is primarily due to the development of new technologies, globalization and digitalization. That is, education should be digitalized, distance education should be provided. The use of distance learning should not become a subject for discussion. We need to think about the quality of distance education.